2014
DOI: 10.22610/jebs.v6i3.487
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Level of Financial Literacy among South African Undergraduate Students

Abstract: The purpose of the study was twofold: to examine the relationship between financial literacy and demographic and other socioeconomic factors of a sample of undergraduate students; and to evaluate how undergraduate students' financial knowledge correlate with their attitude and behavior towards personal finance issues. A structured questionnaire was used to collect data and logistic regression and Chi-Square statistical procedures were employed to analyse the data using the Statistical Package for Social Scient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 12 publications
2
20
0
3
Order By: Relevance
“…While Thapa (2015) found that there is no significant relationship between gender and financial capability, while Agnew and concluded that gender was the only consistent factor in understanding college students' debt behaviours in both New Zealand and England. This was similar to findings of some South African studies which found gender to be statistically significant among students studying accounting degrees in South African universities (De Clercq and Venter, 2009;Oseifuah and Gyekye, 2014). In addition, while Oseifuah and Gyekye ( 2014) further asserts that male students at the University of Limpopo are more financially capable than female, this finding was in contrast with (Fatoki, 2014), who found that female students enrolled in a non-business degree at two South African universities had better financial capability than their male counterparts.…”
Section: Literature Reviewsupporting
confidence: 84%
See 1 more Smart Citation
“…While Thapa (2015) found that there is no significant relationship between gender and financial capability, while Agnew and concluded that gender was the only consistent factor in understanding college students' debt behaviours in both New Zealand and England. This was similar to findings of some South African studies which found gender to be statistically significant among students studying accounting degrees in South African universities (De Clercq and Venter, 2009;Oseifuah and Gyekye, 2014). In addition, while Oseifuah and Gyekye ( 2014) further asserts that male students at the University of Limpopo are more financially capable than female, this finding was in contrast with (Fatoki, 2014), who found that female students enrolled in a non-business degree at two South African universities had better financial capability than their male counterparts.…”
Section: Literature Reviewsupporting
confidence: 84%
“…This finding is consistent with some existing studies (Thapa, 2015). However, other studies have found that there is a positive relationship between gender and financial capabilities (De Clercq and Venter, 2009;Oseifuah and Gyekye, 2014;Agnew and Harrison, 2015). Whilst several studies have concluded that male students are more financially capable than female students (Oseifuah and Gyekye, 2014;Montford and Goldsmith, 2016;Bucher-Koenen et al, 2017;Chen and Garand, 2018), a few have asserted that female students are better equipped to make financial decisions than male students (Shaari et al, 2013;Fatoki, 2014).…”
Section: Gendermentioning
confidence: 99%
“…Higher levels of financial literacy were found among the subgroup of students who financed their university education through bank loans compared to the groups that financed their studies through financial support by family The study also found that students who participated in family financial decisions and those who have taken money management course are more likely to be financially literate (Oseifuah and Gyekye 2014). Literature shows women are less financially literate and less like to plan for future and have less financial experiences although live long life as compared to male, who have more financial experiences (Lusardi and Mitchell 2018).…”
Section: Literature Reviewmentioning
confidence: 76%
“…Similarly, social factors are education (Agarwalla et al, 2015), language, religion, ethnicity (Klapper et al, 2012), etc. Some of demographic variables are sex (Oseifuah & Gyekye, 2014), age (Zadeh & Dahmardeh, 2013), marital status (Ravikumar, 2013), etc. Some of the personal economic factors are income level (Consumer Financial Protection Bureau, 2014) and occupation (Atakora, 2013).…”
Section: Determinants Of Financial Behaviourmentioning
confidence: 99%